The Charting Implications of IALA Buoyage System "A" - Pielou, F. A. (The International Hydrographic Review, 2015)
As Superintendent of Chart Maintenance at the UK Hydrographic Department, the author has been actively engaged in the discussions since 1975 with the International Association of Lighthouse Authorities to determine the hydrographic implications of the introduction of the new IALA Buoyage System " A ". His paper outlines the effects on charts and other hydrographic publications, the problems of acquiring the data and the need for a co-ordinated programme to ensure the buoyage changes and chart amendments keep in step.